Structural Constraints in the Implementation of Child-Friendly Education in Islamic Boarding Schools - Nurhasanah Bakhtiar; Zuhairansyah Arifin; Afrida; Nurul Khairani Islami; Musa Thahir (Yogyakarta: Jurusan Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2025)
Purpose – The implementation of child-friendly education in Islamic boarding schools (pesantren) faces various structural challenges that remain underexplored in existing studies. This study aims to analyze the characteristics and implications of structural constraints in the implementation of child-friendly education programs in Islamic boarding schools. Design/methods/approach – The research employed a qualitative descriptive approach across nine Islamic boarding schools in Riau and the Riau Islands Province, Indonesia. Data were collected through observations and in-depth interviews. The key informants consisted of four government authorities, nine leaders, and nine students. Data analysis in this study follows thematic analysis based on the Miles & Huberman model, which consists of data condensation, data display, and conclusion drawing and verification. Findings – The study identifies three major structural constraints. First, limited government support reflects weak policy integration between the state and Islamic boarding schools, resulting in insufficient resources and program support. Second, the misalignment between pesantren institutional regulations and child-friendly education principles contributes to the structural neglect of children's rights. Third, the temporary nature of stakeholder collaboration highlights weak inter-institutional coordination. Research implications/limitations – The study was limited to a specific regional context, which may differ from that in other areas. Future research should broaden its scope by involving a larger number of pesantren across comparative contexts. Originality/value – This study provides original insights by highlighting structural constraints that are often overlooked in studies of child-friendly education in Islamic boarding schools. By focusing on institutional and policy dimensions, the research offers a novel perspective beyond normative and cultural discussions in the existing literature.